FOREWORD - Sibaja-Cordero, Jeffrey A. (2022)
The Revista de Biología Tropical is an international scientific publication edited by the University of Costa Rica since 1953. This supplement is titled “70th Anniversary of the Revista de Biología Tropical” and comprises seven academic papers. The primary objective was to compile information on the topics published over this period. Historical aspects preceding the founding of the Journal are also mentioned, which fostered the development of Tropical Biology in this Central American country.